Improving Spatial Thinking Skills through GEE-Integrated STEM Learning: A Quasi-Experimental Study among Geography Undergraduates - Haris Haris; Syamsunardi; Abdul Mannan; Nurul Ilmi Rasjusti (Jurusan Teknik Informatika dan Komputer, 2025)
This study examines the effectiveness of integrating Google Earth Engine (GEE) into a STEM-based learning framework to enhance the spatial thinking skills of geography undergraduates. A quasi-experimental design involving 60 students was implemented, with one class assigned to the experimental group receiving GEE-integrated STEM instruction and the other to the control group receiving conventional instruction. Spatial thinking outcomes were measured using pretest–posttest cognitive assessments and four performance indicators: spatial representation, spatial relation, spatial analysis, and spatial application. Data analysis included descriptive statistics, normality and homogeneity tests, paired-sample t-tests, independent-sample t-tests, Cohen’s d effect size, and ANCOVA controlling for pretest scores. The results indicate that the experimental group achieved significantly higher posttest scores than the control group (t(58) = 10.24, p < 0.001), with a large effect size (d = 2.64). ANCOVA further confirmed the robustness of the treatment effect after adjusting for initial differences (F(1,57) = 101.99, p < 0.001). Indicator-level analysis also showed consistent improvement across all spatial thinking components. This study is limited by its single-institution context, quasi-experimental design, and potential novelty effects associated with geospatial technology integration. Future research should involve larger and more diverse samples to validate these findings.